2001
DOI: 10.1038/84159
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Many peptide hormones elicit a wide array of physiological effects by binding to G-protein coupled receptors. We have determined the conformation of pituitary adenylate cyclase activating polypeptide, PACAP(1--21)NH(2), bound to a PACAP-specific receptor by NMR spectroscopy. Residues 3--7 form a unique beta-coil structure that is preceded by an N-terminal extended tail. This beta-coil creates a patch of hydrophobic residues that is important for receptor binding. In contrast, the C-terminal region (residues 8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
96
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(102 citation statements)
references
References 26 publications
6
96
0
Order By: Relevance
“…Typically the N-terminal segment of the ligand is responsible for receptor signaling, whereas the C-terminal segment is an important determinant for the receptor binding (45,46) and may interact with the ECD1 of the receptor as evidenced by cross-linking (47). Furthermore, the bioactive conformations of various peptide hormones are proposed to be of amphipathic helical nature (48), similar to the conformation observed for astressin. The 3D structure of ECD1 of CRF-R2␤ in complex with astressin elucidates the major determinants and the physical basis for the ligand binding affinity and specificity for CRF receptors, which are crucial components toward an understanding of diverse biological functions of the CRF ligand/receptor system.…”
Section: Crf Ligand-receptor Interactions Have a Common Binding Modementioning
confidence: 94%
“…Typically the N-terminal segment of the ligand is responsible for receptor signaling, whereas the C-terminal segment is an important determinant for the receptor binding (45,46) and may interact with the ECD1 of the receptor as evidenced by cross-linking (47). Furthermore, the bioactive conformations of various peptide hormones are proposed to be of amphipathic helical nature (48), similar to the conformation observed for astressin. The 3D structure of ECD1 of CRF-R2␤ in complex with astressin elucidates the major determinants and the physical basis for the ligand binding affinity and specificity for CRF receptors, which are crucial components toward an understanding of diverse biological functions of the CRF ligand/receptor system.…”
Section: Crf Ligand-receptor Interactions Have a Common Binding Modementioning
confidence: 94%
“…In contrast, mutational mapping of ligand-binding sites in peptide receptors indicates that extracellular domains are also involved in ligand recognition (2). To date, direct structural information regarding ligand binding and GPCR activation is very limited (6). Targeted drug design is restricted to computational methods and other ligand design approaches to find and optimize lead compounds (7).…”
mentioning
confidence: 99%
“…The high affinity of the ligand to its receptor has precluded the elucidation of the receptor-bound ligand conformation by solution-state NMR (see, for example, ref. 6). A recent NMR study in the presence of detergent reported NT(8-13) chemical shift changes upon receptor interaction (18,19).…”
mentioning
confidence: 99%
“…Therefore, it has been suggested that the conformation, location, and orientation of the ligand in the membrane are critical in determining its ability to reach and interact productively with its site of action (3)(4)(5). Exploring the conformational and dynamic properties of these ligands in the membrane can lead to a better understanding of the molecular features involved in their interactions with the target proteins (6).…”
mentioning
confidence: 99%